Mainstreaming Human Rights in the Asian Judiciary - Desi Hanara (The Constitutional Court of the Republic of Indonesia, 2018)
Human rights protection in Asia is hindered by the absence of binding human rights instruments and enforcement mechanisms, including the lack of human rights mainstreaming into the works of relevant stakeholders, notably the judiciary. Judiciary plays key roles in the realization and protection of human rights. As the guardian of the Constitution, the Indonesian Constitutional Court (‘the Court’) is mandated to protect the human rights of the citizens. This paper argues that the Court, which previously served as the President of the Association of Asian Constitutional Courts and Equivalent Institutions (AACC), has the potential to play a leading role in mainstreaming human rights in the region. Using normative and comparative legal research methodologies, the paper identified the Court’s mandates on human rights at the national, regional and international levels; assessed the need for human rights mainstreaming in the Asian judiciary; and examined the significant potential of the AACC to house the mainstreaming project. Finally, it proposes several recommendations for the Court’s consideration, namely to encourage judicial independence, recommend human rights incorporation into judicial discussions and decisions, suggest the establishment of a platform to enhance human rights expertise of the judiciary, as well as facilitate a platform for the development of binding human rights instruments and the establishment of an Asian Human Rights Court.